Phyllosphere synthetic microbial communities: a new frontier in plant protection - Easton Sarver; Kevin J. González-Morelo; Katie G. Christensen; Hanna M. Lefevers; Kendall R. Corbin (BMC Plant Biology)
Abstract Background The phyllosphere, which includes the surfaces of plant leaves and stems, is one of the largest and most diverse microbial habitats on Earth, yet it remains understudied in plant-microbe interaction research. Recent studies have highlighted the significant role of phyllosphere epiphytic bacteria in enhancing plant health. These microorganisms help improve nutrient uptake, defend against pathogens, and increase resilience to environmental stressors. Main body In recent years, phyllosphere-associated microorganisms have been assembled into synthetic microbial communities (SynComs) to replicate or augment natural microbial populations. This review examines the emerging field of phyllosphere-modulating synthetic communities (PMS) and their potential to enhance plant fitness and protection. We explore the latest advancements in the design of SynComs, with a focus on their agricultural applications. Despite promising results, a consensus is lacking on best practices for standardizing the development and application of PMS, with the complexity of PMS reported in the literature ranging from a few species to as many as 48 core phyla, including Proteobacteria, Firmicutes, and Actinobacteria. Conclusion While PMS present a promising alternative to conventional plant protection methods, their full potential remains underexplored. Continued efforts to standardize and refine phyllosphere-modulating SynComs are essential to establishing them as reliable biological tools for improving plant health.